Artificial stone with 3D texture effect and preparation method thereof
By using specific processes such as expandable microspheres and PMMA resin liquid, artificial stone materials with 3D texture effects were prepared, which solved the problem of the lack of three-dimensional texture of the existing artificial stone materials, and achieved high realistic and comfortable feeling. Effect.
Patent Information
- Application Number
- CN202411447047.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-16
- Publication Date
- 2025-02-07
AI Technical Summary
The existing artificial stone materials lack 3D texture effects, resulting in low simulation and insufficient three-dimensional texture, which cannot bring consumers a good visual reality and comfortable experience.
The main material A and auxiliary material B, which include expandable microspheres, PMMA resin liquid, crosslinking agents, etc., are prepared by a specific stirring and vacuum defoaming process.
It realizes the significant 3D texture concave and convex effect of artificial stone slabs, bringing users a comfortable touch and a good visual reality, and is suitable for a variety of decoration and design fields.
Abstract
Description
Technical Field
[0001] The invention relates to an artificial stone, in particular to an artificial stone with a 3D texture effect and a preparation method thereof. Background Art
[0002] Stone materials used as decorative materials are generally divided into natural stone and artificial stone. Natural stone, such as marble, also known as marble, has beautiful textures and bright colors, and is widely used in building interior walls. The radioactive element content of natural marble often exceeds the standard, which will cause harm to the human body, but artificial stone does not have this problem; natural marble is easy to break and difficult to process, while artificial stone uses resin with high elongation at break and good toughness (such as acrylic resin) as the base material, which is easy to process and not easy to break. At present, artificial stone has been widely used in living rooms, conference rooms, offices, lounges and bathrooms in many places such as civil aviation airports, banks, hotels, hotels, companies, office buildings, etc. It is also widely used in home decoration, such as artificial stone countertops, kitchen cabinets, sanitary ware and other fields.
[0003] The representative varieties of Chinese artificial stone solid surface patterned plates include netted stone, phoenix tail stone, wood grain stone, multi-color artificial textured stone, etc. Most of its production processes are: pouring the mixed slurries of various colors into the mold in sequence or at one time with the help of equipment, and then pushing them into the vacuum box to evacuate, and then curing and forming them after leaving the box. The artificial stone patterned plates produced by the above process have the disadvantages of low simulation degree and insufficient three-dimensional texture, which leads to the current artificial stone not having a good 3D texture effect and concave and convex texture, which can bring consumers a good sense of reality and comfort in experience in use. Summary of the invention
[0004] The purpose of the present invention is to provide an artificial stone with a 3D texture effect and a preparation method thereof, aiming to solve the above-mentioned problems.
[0005] In order to achieve the above object, the technical solution adopted by the present invention is as follows:
[0006] In a first aspect, the present invention provides a 3D texture effect artificial stone, wherein the 3D texture effect artificial stone comprises a main material component A and an auxiliary material component B;
[0007] The raw materials for preparing the main material A component include the following components by weight percentage: 0-10% expandable microspheres, 0-5% A pigment, 30-50% PMMA resin liquid, 0.1-1% crosslinking agent, 0.1-1% accelerator, 0.01-0.5% chain transfer agent, 0.1-1% initiator, 50-70% filler, and 0-5% diluent monomer;
[0008] The raw materials for preparing the auxiliary material component B include the following components by weight percentage: 0.5-10% expandable microspheres, 0-5% B pigment, 30-50% PMMA resin liquid, 0.1-1% crosslinking agent, 0.1-1% accelerator, 0.01-0.5% chain transfer agent, 0.1-1% initiator, 50-70% filler, and 0-5% diluent monomer.
[0009] Preferably, the A pigment includes titanium dioxide slurry and carbon black slurry; and the B pigment is titanium dioxide slurry.
[0010] Preferably, the crosslinking agent is ethylene glycol dimethyl methacrylate.
[0011] Preferably, the accelerator is calcium hydroxide.
[0012] Preferably, the chain transfer agent is ethylene glycol dimercaptoacetate.
[0013] Preferably, the initiator is tert-butyl permaleate.
[0014] Preferably, the filler is any one of aluminum hydroxide (ATH), magnesium hydroxide or calcium carbonate.
[0015] Preferably, the diluent monomer is methyl methacrylate or methacrylate.
[0016] Preferably, the preparation method of the main ingredient A component specifically includes:
[0017] Put the PMMA resin liquid in a container, add A pigment, crosslinking agent, accelerator and chain transfer agent in sequence at a dispersing speed of 500r / min; then add filler, expandable microspheres and diluent monomer in sequence at a speed of 1000r / min; then stir at a speed of 2000-2500r / min, and heat the resin mixture to 30-32°C by the heat generated by high-speed dispersion; then add initiator, stir at a speed of 1000r / min for 30s, and then transfer to a vacuum device to be stirred; after vacuuming for 2min and degassing at a speed of 50-100r / min, release the vacuum to obtain the main material A component;
[0018] The preparation method of the auxiliary material B component specifically includes:
[0019] Put the PMMA resin liquid in a container, add the B pigment, crosslinking agent, accelerator and chain transfer agent in sequence at a dispersion speed of 500 r / min; then add the filler, expandable microspheres and diluent monomer in sequence at a speed of 1000 r / min; then stir at a speed of 2000-2500 r / min, and heat the resin mixture to 30-32° C. by the heat generated by high-speed dispersion; then add the initiator, stir at a speed of 1000 r / min for 30 seconds, and then transfer to a vacuum device to be stirred; after vacuuming for 2 minutes and degassing at a speed of 50-100 r / min, release the vacuum to obtain the auxiliary material B component.
[0020] In a second aspect, the present invention further provides a method for preparing an artificial stone with a 3D texture effect, the preparation method comprising:
[0021] The main material component A and the auxiliary material component B are mixed and stirred in a mass ratio of 1:1 to obtain a patterned color mixture;
[0022] The obtained pattern color mixture is poured into a mold to obtain a material layer with a thickness of 2 to 3 mm;
[0023] pouring the main material A component again onto the upper layer of the material layer to obtain a solidified product;
[0024] The obtained solidified material is cooled and roughly processed, and the side in contact with the bottom of the mold is taken as the front side of the artificial stone, and then finely processed to obtain an artificial stone with a strip-shaped texture;
[0025] The obtained artificial stone with strip-shaped texture is heat-treated and cooled to obtain an artificial stone with 3D texture effect.
[0026] In summary, due to the adoption of the above technical solution, the beneficial effects of the present invention are:
[0027] The artificial stone plate prepared by the present invention has a significant 3D texture concave-convex effect, can give people a comfortable 3D concave-convex touch during use, can give consumers a good visual sense of reality and a comfortable experience in use. It can be widely used in the design and manufacture of artificial stone application fields such as artificial stone office desks, furniture facings, commercial housing interior decoration, commercial building interior design, etc. DETAILED DESCRIPTION
[0028] In order to further understand the present invention, preferred embodiments of the present invention are described below in conjunction with examples. However, it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention, rather than limiting the claims of the present invention.
[0029] The raw material information used in the embodiments of the present invention is as follows:
[0030] Expandable microspheres: Nouryon 051DU40;
[0031] Titanium dioxide: Longman Baili R996 titanium dioxide;
[0032] Aliphatic unsaturated resin: No. 1 aliphatic unsaturated resin from Guangzhou Sihe Composite Materials Co., Ltd.;
[0033] Carbon black: Cabot M800 carbon black;
[0034] Ethylene glycol dimethyl methacrylate: Evonik Degussa;
[0035] Calcium hydroxide: Hengshui Huayao Technology Co., Ltd., analytical grade;
[0036] Ethylene glycol dimercaptoacetate: Shanghai Youpeng Chemical Co., Ltd.;
[0037] Aluminum hydroxide (ATH): Zhongzhou Chalco New Materials H-WF-25B-SP;
[0038] Methyl methacrylate: Sinopec;
[0039] Tert-butyl peroxymaleate: Cat.~40 from Shanghai Stillime New Building Materials Co., Ltd.
[0040] Example 1
[0041] The embodiment of the present invention discloses a 3D texture effect artificial stone. The 3D texture effect artificial stone comprises a main material A component and an auxiliary material B component.
[0042] The raw materials for preparing the main ingredient A component include the following components by weight percentage: 0.5% expandable microspheres, 0.7% A pigment, 35% PMMA resin liquid, 0.45% crosslinking agent, 0.2% accelerator, 0.05% chain transfer agent, 0.3% initiator, 61.5% filler, and 1.3% diluent monomer;
[0043] The raw materials for preparing the auxiliary material component B include the following components by weight percentage: 2% expandable microspheres, 1.5% B pigment, 35% PMMA resin liquid, 0.45% crosslinking agent, 0.2% accelerator, 0.05% chain transfer agent, 0.3% initiator, 60% filler, and 0.5% diluent monomer.
[0044] Wherein, the A pigment includes titanium dioxide paste and carbon black paste, and according to the weight percentage of the raw materials for preparing component A: titanium dioxide paste 0.2%, carbon black paste 0.5%; the B pigment is titanium dioxide paste, the crosslinking agent is ethylene glycol dimethyl methacrylate, the accelerator is calcium hydroxide, the chain transfer agent is ethylene glycol dimercaptoacetate, the initiator is tert-butyl peroxymaleate, the filler is any one of aluminum hydroxide (ATH), magnesium hydroxide or calcium carbonate, the diluent monomer is methyl methacrylate or methacrylate, and the expandable microspheres are 051DU40.
[0045] The expanded microspheres generally have a core-shell structure, generally composed of a polymer shell and an unstable core. The expanded microspheres are regular or irregular spherical shapes, and the initial diameter of the microspheres can range from 5 to 100 μm. When the expanded microspheres are heated to the glass transition temperature of the shell polymer, they begin to gradually expand, and this temperature is recorded as Ts; if the heating continues, its volume will continue to expand, and its shell will rapidly become thinner and form a hollow ball, and the final expansion ratio is 10 to 100 times, and this temperature is recorded as Tmax; when the heating temperature exceeds Tmax or is heated for a long time, the spheres will shrink or break. The expanded microspheres used in the present invention have a Ts of 100 to 160°C and a Tmax of 150 to 220°C.
[0046] The mass ratio of the main material component A to the auxiliary material component B is 5:1. The PMMA resin liquid is prepared by the following preparation method: PMMA is dissolved in MMA, and the amount of PMMA is 20% of the mass fraction of the monomer MMA to obtain PMMA resin liquid. The titanium dioxide paste is prepared by the following preparation method: 50% titanium dioxide and 50% aliphatic unsaturated resin are mixed according to weight percentage to obtain titanium dioxide paste. The carbon black paste is prepared by the following preparation method: 20% carbon black and 80% PMMA resin liquid are mixed according to weight percentage to obtain carbon black paste.
[0047] The main material A component is prepared by the following preparation method: placing PMMA resin liquid in a container, and adding titanium dioxide slurry, carbon black slurry, ethylene glycol dimethacrylate, calcium hydroxide and ethylene glycol dimercaptoacetate in sequence at a dispersion speed of 500 r / min; then adding aluminum hydroxide powder, expandable microspheres and MMA in sequence at a speed of 1000 r / min; then stirring at a speed of 2000-2500 r / min, and heating the resin mixture to 30-32° C. by the heat generated by high-speed dispersion; then adding tert-butyl peroxymaleate, stirring at a speed of 1000 r / min for 30 seconds, and then transferring to a vacuum device to be stirred; after vacuuming for 2 minutes and degassing at a speed of 50-100 r / min, the vacuum is released to obtain the main material A component, and the main material A component accounts for the largest proportion of the mass of the artificial stone plate, and the appearance is mostly a continuous area;
[0048] The preparation method of the auxiliary material component B comprises: placing PMMA resin liquid in a container, and adding titanium dioxide slurry, ethylene glycol dimethacrylate, calcium hydroxide and ethylene glycol dimercaptoacetate in sequence at a dispersion speed of 500 r / min; then adding aluminum hydroxide powder, expandable microspheres and MMA in sequence at a rotation speed of 1000 r / min; then stirring at a rotation speed of 2000-2500 r / min, and heating the resin mixture to 30-32° C. by the heat generated by high-speed dispersion; then adding tert-butyl peroxymaleate, stirring at a rotation speed of 1000 r / min for 30 seconds and then transferring to a vacuum device to be stirred; after vacuuming for 2 minutes and degassing at a rotation speed of 50-100 r / min, the vacuum is released to obtain the auxiliary material component B, which is a small portion of the mass of the artificial stone slab and can be a combination of one or more. The appearance is mostly non-continuous areas, and mainly forms decorative patterns with strip-like, rib-like, grid-like and other effects.
[0049] The preparation method of the 3D texture effect artificial stone comprises the following steps:
[0050] Step S1: prepare 1000 grams of the main ingredient A component and 200 grams of the auxiliary ingredient B component; take 200 grams of the main ingredient A component, and mix and stir the main ingredient A component and the auxiliary ingredient B component according to a mass ratio of 1:1. The specific steps are: put 200 grams of the main ingredient A component and 200 grams of the auxiliary ingredient B component in a mixing container, 200 grams of the main ingredient A component is arranged at the bottom of the mixing container, and 200 grams of the auxiliary ingredient B component is arranged on the top of the main ingredient A component, and pour and mix vertically (h: ~ 30cm) in the mixing container, put a glass rod in the mixing container (the glass rod is in contact with the bottom of the mixing container), gently stir clockwise for 2 to 3 times, and then remove it to obtain a patterned color mixture;
[0051] Step S2: pouring the obtained pattern color mixture into a mold with a PE soft film lining of 130 mm × 280 mm × 15 mm in size, and pouring the pattern color mixture vertically (h: ~ 20 cm) to pour the slurry into a thin stream with a diameter of 3 to 5 mm, moving from one side of the mold to the other side of the mold, moving back and forth until a 2 to 3 mm thick material layer is formed at the bottom of the mold;
[0052] Step S3: pouring 800 g of the main material A component onto the upper layer of the material layer again to obtain a solidified product; preheating the inner cavity of the mold to 40° C., and then covering the top of the mixture of the main material A component and the material layer with a PET film to isolate it from the air, and the mixture solidifies within 15 minutes;
[0053] Step S4: cooling and rough processing the obtained solidified material, the rough processing specifically includes placing the cooled solidified material in a rotary sander for rough processing, taking the side in contact with the bottom of the mold as the front side of the artificial stone; and then fine processing, the fine processing specifically includes grinding with sandpaper of gradually finer grains, and finally grinding with 600# grain size to obtain an artificial stone with a strip-shaped texture (the plate thickness is controlled at 12±0.2mm);
[0054] Step S5: heat-treating and cooling the obtained artificial stone with strip-shaped texture. Specifically, the artificial stone is placed in a heating container, the heating container is pre-heated to 150°C, and the artificial stone is placed in the heating container at a constant temperature for 25 minutes, so that the 3D texture additive in the artificial stone plate expands under heat treatment to form a 3D texture effect with a concave and convex touch. After the constant temperature is completed, the artificial stone is taken out of the oven and placed at room temperature to cool to room temperature to obtain an artificial stone with a 3D texture effect. The appearance texture formed by the 3D texture effect artificial stone can be a strip-like shape similar to wood grain, or a vein-like shape similar to marble, or a grid-like decorative effect pattern.
[0055] For the subsequent evaluation of 3D texture effect, the 3D texture effect artificial stone obtained in Example 1 is recorded as test block 1A.
[0056] Example 2
[0057] The embodiment of the present invention discloses a 3D texture effect artificial stone. The 3D texture effect artificial stone comprises a main material A component and an auxiliary material B component.
[0058] The raw materials for preparing the main ingredient A component include the following components by weight percentage: 0.5% expandable microspheres, 0.7% A pigment, 35% PMMA resin liquid, 0.45% crosslinking agent, 0.2% accelerator, 0.05% chain transfer agent, 0.3% initiator, 61.5% filler, and 1.3% diluent monomer;
[0059] The raw materials for preparing the auxiliary material component B include the following components by weight percentage: 5% expandable microspheres, 1.5% B pigment, 35% PMMA resin liquid, 0.45% crosslinking agent, 0.2% accelerator, 0.05% chain transfer agent, 0.3% initiator, 57% filler, and 0.5% diluent monomer.
[0060] Wherein, the A pigment includes titanium dioxide paste and carbon black paste, and according to the weight percentage of the raw materials for preparing component A: titanium dioxide paste 0.2%, carbon black paste 0.5%; the B pigment is titanium dioxide paste, the crosslinking agent is ethylene glycol dimethyl methacrylate, the accelerator is calcium hydroxide, the chain transfer agent is ethylene glycol dimercaptoacetate, the initiator is tert-butyl peroxymaleate, the filler is any one of aluminum hydroxide (ATH), magnesium hydroxide or calcium carbonate, the diluent monomer is methyl methacrylate or methacrylate, and the expandable microspheres are 051DU40;
[0061] The mass ratio of the main material component A to the auxiliary material component B is 5:1, and the PMMA resin liquid is prepared by the same method as in Example 1. The titanium white slurry is prepared by the same method as in Example 1. The carbon black slurry is prepared by the same method as in Example 1.
[0062] The preparation method of the main material A component is the same as that of Example 1. The preparation method of the auxiliary material B component is the same as that of Example 1.
[0063] For the subsequent evaluation of 3D texture effect, the 3D texture effect artificial stone obtained in Example 2 is recorded as test block 2A.
[0064] The preparation method of the 3D texture effect artificial stone is the same as that of Example 1.
[0065] Example 3
[0066] The embodiment of the present invention discloses a 3D texture effect artificial stone. The 3D texture effect artificial stone comprises a main material A component and an auxiliary material B component.
[0067] The raw materials for preparing the main ingredient A component include the following components by weight percentage: 0% expandable microspheres, 0.7% A pigment, 35% PMMA resin liquid, 0.45% crosslinking agent, 0.2% accelerator, 0.05% chain transfer agent, 0.3% initiator, 62% filler, and 1.3% diluent monomer;
[0068] The raw materials for preparing the auxiliary material component B include the following components by weight percentage: 7% expandable microspheres, 1.5% B pigment, 35% PMMA resin liquid, 0.45% crosslinking agent, 0.2% accelerator, 0.05% chain transfer agent, 0.3% initiator, 55% filler, and 0.5% diluent monomer.
[0069] Wherein, the A pigment includes titanium dioxide paste and carbon black paste, and according to the weight percentage of the raw materials for preparing component A: titanium dioxide paste 0.2%, carbon black paste 0.5%; the B pigment is titanium dioxide paste, the crosslinking agent is ethylene glycol dimethyl methacrylate, the accelerator is calcium hydroxide, the chain transfer agent is ethylene glycol dimercaptoacetate, the initiator is tert-butyl peroxymaleate, the filler is any one of aluminum hydroxide (ATH), magnesium hydroxide or calcium carbonate, the diluent monomer is methyl methacrylate or methacrylate, and the expandable microspheres are 051DU40.
[0070] The mass ratio of the main material component A to the auxiliary material component B is 5:1, and the PMMA resin liquid is prepared by the same method as in Example 1. The titanium white slurry is prepared by the same method as in Example 1. The carbon black slurry is prepared by the same method as in Example 1.
[0071] The preparation method of the main material A component is the same as that of Example 1. The preparation method of the auxiliary material B component is the same as that of Example 1. The preparation method of the 3D texture effect artificial stone is the same as that of Example 1.
[0072] For the subsequent evaluation of 3D texture effect, the 3D texture effect artificial stone obtained in Example 3 is recorded as test block 3A.
[0073] Example 4
[0074] The only difference between Example 4 and Example 1 is that the raw materials for preparing the main ingredient A component include the following components in percentage by weight: 7% expandable microspheres, 1.5% A pigment, 35% PMMA resin liquid, 0.45% cross-linking agent, 0.2% accelerator, 0.05% chain transfer agent, 0.3% initiator, 55% filler, and 0.5% diluent monomer.
[0075] Comparative Example 1
[0076] In this comparative example, a 3D texture effect artificial stone is provided, and its preparation method is the same as the preparation method in Example 1, except that expandable microspheres are not added in this comparative example.
[0077] The 3D texture effect artificial stone includes main material A component and auxiliary material B component:
[0078] The raw materials for preparing the main ingredient A component include the following components by weight percentage: 0.7% A pigment, 35% PMMA resin liquid, 0.45% crosslinking agent, 0.2% accelerator, 0.05% chain transfer agent, 0.3% initiator, 62% filler, and 1.3% diluent monomer;
[0079] The raw materials for preparing the auxiliary material B component include the following components by weight percentage: 1.5% B pigment, 35% PMMA resin liquid, 0.45% crosslinking agent, 0.2% accelerator, 0.05% chain transfer agent, 0.3% initiator, 62% filler, and 0.5% diluent monomer.
[0080] Wherein, the A pigment includes titanium dioxide paste and carbon black paste, and according to the weight percentage of the raw materials for preparing component A: titanium dioxide paste 0.2%, carbon black paste 0.5%; the B pigment is titanium dioxide paste, the crosslinking agent is ethylene glycol dimethyl methacrylate, the accelerator is calcium hydroxide, the chain transfer agent is ethylene glycol dimercaptoacetate, the initiator is tert-butyl peroxymaleate, the filler is any one of aluminum hydroxide (ATH), magnesium hydroxide or calcium carbonate, the diluent monomer is methyl methacrylate or methacrylate, and the expandable microspheres are 051DU40.
[0081] The mass ratio of the main material component A to the auxiliary material component B is 5:1, and the PMMA resin liquid is prepared by the same method as in Example 1. The titanium white slurry is prepared by the same method as in Example 1. The carbon black slurry is prepared by the same method as in Example 1.
[0082] The preparation method of the main material A component is the same as that of Example 1. The preparation method of the auxiliary material B component is the same as that of Example 1.
[0083] The preparation method of the 3D texture effect artificial stone is the same as that of Example 1.
[0084] For the subsequent evaluation of 3D texture effect, the 3D texture effect artificial stone obtained in Comparative Example 1 is recorded as test block 1B.
[0085] 3D texture effect evaluation:
[0086] The thickness of the thickest and thinnest areas of the test block 1A prepared in Example 1, the test block 2A prepared in Example 2, the test block 3A prepared in Example 3, and the test block 1B prepared in Comparative Example 1 were measured using a vernier caliper, and the difference was calculated to obtain the △h value. The size of △h was used to reflect the concave and convex presentation effect of the 3D texture. The results are shown in Table 1.
[0087] Table 1: △h value of 3D texture effect artificial stone samples
[0088] Example Test block number △h Example 1 Test Block 1A 0.4mm Comparative Example 1 Test Block 1B 0.0mm Example 2 Test Block 2A 1.2mm Example 3 Test Block 3A 1.3mm
[0089] According to the △h values of the test blocks obtained in Example 1, Example 2, Example 3 and Comparative Example 1, the artificial stone plate prepared by the present invention has a significant 3D texture concave-convex effect. It can give people a comfortable 3D concave-convex touch during use, and can bring consumers a good sense of reality and a comfortable experience in use. It can be widely used in the design and manufacture of artificial stone application fields such as artificial stone office desktops, furniture facings, commercial housing interior decoration, commercial building interior design, etc.
[0090] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.
Claims
1. A 3D texture effect artificial stone, characterized in that: The 3D texture effect artificial stone comprises a main material component A and an auxiliary material component B; The raw materials for preparing the main material A component include the following components by weight percentage: 0-10% expandable microspheres, 0-5% A pigment, 30-50% PMMA resin liquid, 0.1-1% crosslinking agent, 0.1-1% accelerator, 0.01-0.5% chain transfer agent, 0.1-1% initiator, 50-70% filler, and 0-5% diluent monomer; The raw materials for preparing the auxiliary material component B include the following components by weight percentage: 0.5-10% expandable microspheres, 0-5% B pigment, 30-50% PMMA resin liquid, 0.1-1% crosslinking agent, 0.1-1% accelerator, 0.01-0.5% chain transfer agent, 0.1-1% initiator, 50-70% filler, and 0-5% diluent monomer.
2. The 3D texture effect artificial stone according to claim 1, characterized in that: The A pigment includes titanium dioxide slurry and carbon black slurry; the B pigment is titanium dioxide slurry.
3. The 3D texture effect artificial stone according to claim 1, characterized in that: The crosslinking agent is ethylene glycol dimethyl methacrylate.
4. The 3D texture effect artificial stone according to claim 1, characterized in that: The accelerator is calcium hydroxide.
5. The 3D texture effect artificial stone according to claim 1, characterized in that: The chain transfer agent is ethylene glycol dimercaptoacetate.
6. The 3D texture effect artificial stone according to claim 1, characterized in that: The initiator is tert-butyl permaleate.
7. The 3D texture effect artificial stone according to claim 1, characterized in that: The filler is any one of aluminum hydroxide (ATH), magnesium hydroxide or calcium carbonate.
8. The 3D texture effect artificial stone according to claim 1, characterized in that: The diluent monomer is methyl methacrylate or methacrylate.
9. The 3D texture effect artificial stone according to claim 1, characterized in that: The preparation method of the main ingredient A component specifically includes: Put the PMMA resin liquid in a container, add A pigment, crosslinking agent, accelerator and chain transfer agent in sequence at a dispersing speed of 500r / min; then add filler, expandable microspheres and diluent monomer in sequence at a speed of 1000r / min; then stir at a speed of 2000-2500r / min, and heat the resin mixture to 30-32°C by the heat generated by high-speed dispersion; then add initiator, stir at a speed of 1000r / min for 30s, and then transfer to a vacuum device to be stirred; after vacuuming for 2min and degassing at a speed of 50-100r / min, release the vacuum to obtain the main material A component; The preparation method of the auxiliary material B component specifically includes: Put the PMMA resin liquid in a container, add the B pigment, crosslinking agent, accelerator and chain transfer agent in sequence at a dispersion speed of 500 r / min; then add the filler, expandable microspheres and diluent monomer in sequence at a speed of 1000 r / min; then stir at a speed of 2000-2500 r / min, and heat the resin mixture to 30-32° C. by the heat generated by high-speed dispersion; then add the initiator, stir at a speed of 1000 r / min for 30 seconds, and then transfer to a vacuum device to be stirred; after vacuuming for 2 minutes and degassing at a speed of 50-100 r / min, release the vacuum to obtain the auxiliary material B component.
10. A method for preparing 3D texture effect artificial stone according to any one of claims 1 to 9, characterized in that: The preparation method comprises: The main material component A and the auxiliary material component B are mixed and stirred in a mass ratio of 1:1 to obtain a patterned color mixture; The obtained pattern color mixture is poured into a mold to obtain a material layer with a thickness of 2 to 3 mm; pouring the main material A component again onto the upper layer of the material layer to obtain a solidified product; The obtained solidified material is cooled and roughly processed, and the side in contact with the bottom of the mold is taken as the front side of the artificial stone, and then finely processed to obtain an artificial stone with a strip-shaped texture; The obtained artificial stone with strip-shaped texture is heat-treated and cooled to obtain an artificial stone with 3D texture effect.